Multipoint Problem for B-Parabolic Equations - Ptashnik, B. I.; Tymkiv, I. R. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We establish conditions for the well-posedness of a problem for one class of parabolic equations with the Bessel operator in one of the space variables in a bounded domain with multipoint conditions in the time variable and some boundary conditions in the space coordinates. A solution of the problem is constructed in the form of a series in a system of orthogonalfunctions. We prove a metric theorem on lower bounds for the small denominators appearing in the solution of the problem.